2019
DOI: 10.1097/shk.0000000000001166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Prehospital Red Blood Cell Transfusion on Mortality and Time of Death in Civilian Trauma Patients

Abstract: phRTx was associated with increased survival to hospital, but not overall survival. The "delay death" effect of phRTx carries an impetus to further develop in-hospital strategies to improve survival in severely bleeding patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 34 publications
(17 reference statements)
2
94
0
3
Order By: Relevance
“…In a retrospective study of that system, Rehn and colleagues evaluated outcomes of patients treated with either hypotensive crystalloid resuscitation or PRBCs. Of 539 patients with major haemorrhage, there was no difference in overall mortality between the two groups but there was a significant reduction in prehospital mortality in the PRBC group (27·6% vs. 42·2%) .…”
Section: Modern Prehospital Resuscitationmentioning
confidence: 84%
“…In a retrospective study of that system, Rehn and colleagues evaluated outcomes of patients treated with either hypotensive crystalloid resuscitation or PRBCs. Of 539 patients with major haemorrhage, there was no difference in overall mortality between the two groups but there was a significant reduction in prehospital mortality in the PRBC group (27·6% vs. 42·2%) .…”
Section: Modern Prehospital Resuscitationmentioning
confidence: 84%
“…In total, 47 civilian studies reported on trauma patients. Blunt injury was most prevalent in the included studies, ranging from 55% to 100% of trauma patients . The mean or median injury severity score (ISS) varied from 18 to 43 (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…30,31 At the end of the simulations (minute 240), however, there were very few differences between the crystalloid and prehospital transfusion (PH) simulations for each of the three resuscitation strategies (WB only, CCT only, or WB + CCT). As most trauma patients who die do so in the first 3 hours following admission, 32,33 interventions that prevent derangement of coagulation early in the resuscitation might be beneficial in improving mortality. However, very little of the crystalloid fluid remained in the ECF compartment by the end of the simulation due to ongoing bleeding and fluid redistribution.…”
Section: Discussionmentioning
confidence: 99%